2003
DOI: 10.1364/ol.28.000263
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 355-nm generation in CsB_3O_5 crystal

Abstract: We demonstrate UV generation in CSB3O5 (CBO) crystals grown by the top-seeded solution growth technique. 355-nm UV light was generated by use of a type II CBO crystal as a sum frequency of the fundamental light and the second harmonic of a nanosecond Nd:YVO4 laser. A 3.0-W output of the third-harmonic was obtained at a repetition rate of 31 kHz. The conversion efficiency from the fundamental light to the third harmonic reached 30%, which was 1.5 times higher than that obtained with a type II LiB3O5 crystal und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…In 1993, bulk CBO crystals were obtained from stoichiometric melts and CBO was recognized as a nonlinear optical (NLO) crystal by Wu et al [4]. Having as well as a small walk-off angle in the UV range, CBO crystals are expected to generate more efficient 355 nm light by third harmonic generation (THG) of Nd:YAG laser radiation than LiB 3 O 5 crystals (LBO) which are most generally used for THG [5,6]. Wu et al reported that CBO crystals could be grown from a stoichiometric melt [4] or a slightly Cs 2 O-enriched melt [7].…”
mentioning
confidence: 99%
“…In 1993, bulk CBO crystals were obtained from stoichiometric melts and CBO was recognized as a nonlinear optical (NLO) crystal by Wu et al [4]. Having as well as a small walk-off angle in the UV range, CBO crystals are expected to generate more efficient 355 nm light by third harmonic generation (THG) of Nd:YAG laser radiation than LiB 3 O 5 crystals (LBO) which are most generally used for THG [5,6]. Wu et al reported that CBO crystals could be grown from a stoichiometric melt [4] or a slightly Cs 2 O-enriched melt [7].…”
mentioning
confidence: 99%
“…Instead of widely-used spectro-prism [11,15,16], we use a volume of beam splitting mirrors (characteristics of mirrors M 3 -M 6 are pointed out in Table 1) to separate the fundamental wave, second-harmonic wave and third-harmonic wave, with the advantages of long-distance separation, low astigmatism, parallel output, and thus enabling the reusing of the fundamental wave and second- harmonic wave [17]. We can obtain the fundamental, second-harmonic and third-harmonic laser output simultaneously after the splitting mirrors at different pump current, shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The excellent non-linear optical (NLO) properties of borates are attributed to their various anionic groups, with planar BO 3 and tetrahedral BO 4 groups as basic structures [5], and these BO 3 triangles and BO 4 tetrahedrons can form a variety of compact poly ions by corner sharing of oxygen atoms. At present, though more and more new NLO materials have been discovered [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], these NLO materials have their own drawbacks that limit their application more or less, so the research of other new NLO materials is needed. 4 ] Á 2H 2 O) was reported by Marezio [24] in 1963.…”
Section: Introductionmentioning
confidence: 99%